Ginsenoside Rg1 as an Effective Regulator of Mesenchymal Stem Cells - He, Fang; Yu, Changyin; Liu, Tao; Jia, Huilin (Frontiers in Pharmacology, 2020)
Recently, breakthroughs have been made in the use of mesenchymal stem cells (MSCs) to treat various diseases. Several stem cell types have been authorized as drugs by the European Medicines Agency and the U.S. Food and Drug Administration. The Chinese official document “Notification of the management of stem cell clinical research (trial)” was also published in August 2015. Currently, China has approved 106 official stem cell clinical research filing agencies and 62 clinical research projects, which are mostly focused on MSC therapy. Hence, the optimization and development of stem cell drugs is imperative. During this process, maximizing MSC expansion, minimizing cell loss during MSC transplantation, improving the homing rate, precisely regulating the differentiation of MSCs, and reducing MSC senescence and apoptosis are major issues in MSC preclinical research. Similar to artemisinin extracted from the stems and leaves of Artemisia annua, ginsenoside Rg1 (Rg1) is purified from the root or stem of ginseng. In the human body, Rg1 regulates organ function, which is inseparable from its regulation of adult stem cells. Rg1 treatment may effectively regulate the proliferation, differentiation, senescence and apoptosis of MSCs in different microenvironments in vitro or in vivo. In this review, we discuss recent advances in understanding the effect of Rg1 on MSCs and describe the issues that must be addressed and prospects regarding Rg1 regulation of MSCs in preclinical or clinical studies.